Cognitive network routing algorithm based on service awareness and policy choice - Cheng-jie GU; Shun-yi ZHANG; Yan-fei SUN (Tongxin xuebao)
A cognitive network routing (CNR) algorithm based on service awareness and policy choice oriented to cognitive network was proposed.This algorithm takes network resource,flow,policy choice into account and obtains the flow characteristics and network resources condition in advance.CNR algorithm fulfills the distribution of resources through offline network allocation and gets the optimal path of each flow by online path computation.Simulation verified the effectiveness of cognitive network routing algorithm and showed that compared with the traditional routing algorithms,the cognitive network routing algorithm can improve the cognitive utilization of network resources,avoid network congestion coursed by resources allocation and optimize network performance at different levels.